MICROENCAPSULATION OF PROBIOTICS: TECHNOLOGICAL INNOVATION IN THE FOOD INDUSTRY - Simeoni, Caroline Posser; Etchepare, Mariana de Araújo; Menezes, Cristiano Ragagnin de; Fries, Leadir Martins; Menezes, Maria Fernanda Cáceres; Stefanello, Flávia Santi (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The growing consumer concern about healthy eating led to the development of functional products, ie, that promotes health and well being of consumers beyond their primary nutritional function. The interest by the addition of probiotic microorganisms in various foods has been growing as a way to increase their nutritional and therapeutic values . However, the biggest problem faced by industries in the use of probiotic bacteria in foods is related to the maintenance and viability of these cultures. The probiotic cultures can not survive in sufficiently high number when subjected to certain conditions, for example, storage at low temperatures and the passage through the human gastrointestinal tract. Given this fact, many studies have focused on the protection and viability of probiotic cultures during production, storage and passage through the gastrointestinal tract probiotic product. Studies have shown that the cultures can be significantly protected by microencapsulation technique.